The difference in consumer attitudes of locally grown apples with imported apples. the case of Korca Region, Albania: - Nexhipi, Erjon (Technium Social Sciences Journal, 2022)
What motivates consumers to act differently from each other has been studied and will continue to be studied in order for marketers and consumer attitudes researchers to better understand their needs and, consequently, to satisfy them as best as possible. Figuring out why someone likes a red apple and someone likes a green apple can be a difficult process, but it's still easier than understanding why people choose an imported apple over a domestic apple when no verifiable qualities distinguish them. In attempt to analyze this invisible element and to evidence it, along with other factors such as familiarity with the product, knowledge of the product, physical characteristics, etc. in this study we will prove that there is another evident element and measurable such as the credence attribute for locally produced apples in the Korca area. For the study, 335 random interviews were conducted with apple consumers in the Korca region, providing demographic data, data on consumption, data on knowledge about apples, the attitudes of the interviews about issues related to apples and especially about cultivated apples in Korca. Full analysis was done for descriptive statistical data. Exploratory factor analysis and confirmatory factor analysis were done to group attitudes into fewer factors. The attitudes of the interviewees were grouped into 3 factors, attitudes about the physical qualities of the apple, subjective knowledge and credence attributes of the locally grown apple. Quantitative analysis was done using statistical models binary logistic equation SPSS 26 programs. From this analysis and examination of the relationships of the factors with each other and with other variables in the study, the raised hypotheses of this study were confirmed, Consumers who buy imported apples have a low rating for the Credence attribute "Apple cultivated in the Korca region" and for Subjective knowledge regarding apples.